Feasibility of Administering High-Dose (131)I-MIBG Therapy to Children with High-Risk Neuroblastoma without Lead-Lined Rooms - Chu, Bae P. (Pediatr Blood Cancer, 2016)
BACKGROUND: Although (131)I-metaiodobenzylguanidine therapy ((131)I-MIBG) is increasingly used for children with high-risk neuroblastoma, a paucity of lead-lined rooms limits its wider use. We implemented radiation safety procedures to comply with New York City Department of Health and Mental Hygiene regulations for therapeutic radioisotopes and administered (131)I-MIBG using rolling lead shields. PROCEDURE: Patients received 0.67GBq (18mCi)/kg/dose (131)I-MIBG on an IRB-approved protocol (NCT00107289). Radiation safety procedures included private room with installation of rolling lead shields to maintain area dose rates ≤0.02mSv/h outside the room, patient isolation until dose rate <0.07mSv/h at 1m and retention of a urinary catheter with collection of urine in lead boxes. Parents were permitted in the patient’s room behind lead shields, trained in radiation safety principles and given real-time radiation monitors. RESULTS: Records on 16 (131)I-MIBG infusions among 10 patients (age 2–11 years) were reviewed. Mean ± standard deviation (131)I-MIBG administered was 17.67±11.14 (range: 6.11–40.59) GBq. Mean maximum dose rates outside treatment rooms were 0.013±0.008 mSv/hr. Median time-to-discharge was 3 days post-(131)I-MIBG. Exposure of medical staff and parents was below regulatory limits. Cumulative whole-body dose received by the physician, nurse and radiation safety officer during treatment was 0.098±0.058, 0.056±0.045, 0.055±0.050 mSv respectively. Cumulative exposure to parents was 0.978±0.579mSv. Estimated annual radiation exposure for inpatient nurses was 0.096±0.034mSv/nurse. Thyroid bioassay scans on all medical personnel were <detectable activity. Contamination surveys were <200dpm/100 cm(2). CONCLUSIONS: The use of rolling lead shields and implementation of specific radiation safety procedures allows administration of high-dose (131)I-MIBG and may broaden its use without dedicated lead-lined rooms.